2005
DOI: 10.1088/0031-9155/50/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the photoneutron contamination present in a high-energy radiotherapy treatment room

Abstract: The photoneutron contamination arising from a high-energy medical lineal accelerator is calculated using Monte Carlo simulation, as a function of the radiation field size. The information is used to model the neutron propagation in a radiotherapy treatment room and the transmission across concrete mazes. The Monte Carlo code MCNP4C is used to model the main components of a medical lineal accelerator. Simulations were performed to calculate the photoneutron yields and spectra as a function of the radiation fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…However, out-of-field photo-neutron doses did not change considerably with changing field size. Our findings were also consistent with the results of Al-Ghamdi et al [11], Chibani et al [12] and Garnica-Garza et al [14]. Monte Carlo studies [10,18] also showed that primary collimators made from tungsten alloy has the highest contribution in the photo-neutron production with respect to other components.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, out-of-field photo-neutron doses did not change considerably with changing field size. Our findings were also consistent with the results of Al-Ghamdi et al [11], Chibani et al [12] and Garnica-Garza et al [14]. Monte Carlo studies [10,18] also showed that primary collimators made from tungsten alloy has the highest contribution in the photo-neutron production with respect to other components.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, they claimed that the number of photo-neutron interaction in the collimator system increased and photo-neutron dose proportionally increased. However, Garnica-Garza [14] argued that photo-neutrons were mainly produced in the linear accelerator components at the level of movable or secondary collimators used for modifying field size. Therefore, more photo-neutrons can reach to isocenter without blocked by secondary collimator as the field size increases, and thus photo-neutron dose at central axis increases with the enlargement of field size.…”
Section: Discussionmentioning
confidence: 99%
“…The linear dose-response model of radiation suggests that any increase in dose, no matter how small, results in an increase in risk. Studies of occupational workers exposed to chronic low levels of radiation, above normal background, have shown higher probability with regards to developing leukemia and other cancers 39) . According to annual dose estimations, 3.0 mSv/yr would be received if radiation therapists entered the treatment room immediately after beam-off for a 10 MV PA opposed treatment (Table 1).…”
Section: Dose Rates Versus Timementioning
confidence: 99%
“…Even though the highest estimated annual dose was well below the maximum permissible dose value of 20 mSv/yr, it is still important to reduce the absorbed dose as much as possible so as to lower corresponding risk 39) . However, it is impractical to wait for too long in the clinical situation, as there is a waiting list of patients and tolerance of patients should be considered in terms of delay.…”
Section: Dose Reduction Strategies 1) Optimum Room Entry Timesmentioning
confidence: 99%
“…Regardless of how small the errors in cross-sections or patient geometry representation are, if in the Monte Carlo simulation the proper X-ray spectrum as delivered by the linear accelerator is not being used, the accuracy of the dosimetry will be compromised, in spite of the high precision that the simulation will undoubtedly achieve. Current methods of determining the X-ray spectra delivered by a medical linear accelerator are based mainly on Monte Carlo simulations of the linac head which are lengthy and require very detailed information about the geometry and material composition of the linac head [8][9][10][11][12]. Experimental determination of radiotherapy X-ray spectra is typically carried out by measuring attenuation curves under conditions of narrow beam geometry.…”
Section: Introductionmentioning
confidence: 99%